Borderline Personality Features and Basic Psychological Needs during Adolescence - Armour, Jessie-Ann; Joussemet, Mireille; Varin, Rose; Cavenaghi, Anna; Lelièvre-Blais, Sophie; Mageau, Geneviève A. (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2024)
Objectives: Anchored in self-determination theory, this study investigates the associations between borderline personality disorder (BPD) features and basic psychological need frustration (BPNF) in adolescents.Methods: Participants (N = 270; M age = 15.3) assessed their own BPD features and BPNF through an online questionnaire.Results: Regression analyses revealed that frustrations of relatedness, autonomy, and competence were jointly and uniquely associated with more BPD features in adolescents, controlling for their gender and parents’ education.Implications: These results suggest the importance of taking BPNF into account to better understand the early signs of BPD among adolescents.